The human adventure, Greek and Roman civilization - Educational Research Council of America. Social Science Staff (Boston Allyn and Bacon, 1975)
Text and illustrations trace the evolution of Greek and Roman civilization and their influence on the development of western society.
Includes index.
Keywords: Greece -- Civilization -- To 146 B.C. -- Juvenile literature; Greece -- Civilization -- To 146 B.C.